Effects of Domperidone in Milk Production of Postpartum Mothers with Insufficient Lactation - Samsul Amri, Beni; Mardiah Tahir, Andi; Sriwijaya,; T. Chalid, Maisuri; Tiro, Eddy; Previana, Rina (International Journal of Psychosocial Rehabilitation, 2020)
Breast milk is important for newborn nutrition. Impaired breast milk production in postpartum mothers can affect the growth of newborns.This study aims to investigate the effects of domperidone on newborn birth weight gain and the adverse events of this treatment in postpartum mothers with insufficient lactation.This study is randomized controlled trial was conducted on postpartum mothers with insufficient lactation in the primary health care. The birth weight measured on day 3 after delivery. Each mother was randomized to domperidone 10 mg + vitamin B12 50 mcg or placebo on the 3rd day of postpartum 3 times daily for 7 days. The birth weight is measured every day during the mothers treatment and the side effects on the mother during treatment also recorded.The Results of this study was conducted on 60 postpartum mothers with insufficient lactation. Thirty mothers received domperidone + placebo and 30 mothers received a placebo. The birth weight increased significantly after both domperidone and placebo treatment (p 80%) in both study groups did not experience any side effects.The study Concludes thet weight gain in newborns from postpartum mothers with insufficient lactation increased significantly after 7 days of domperidone administration with minimal adverse events